The fatalistic discourse on immigration in “secure borders”. A methodological proposal for the analysis of propagandistic messages - Rebollo-Bueno, Sara (2023)
Fatalism has gained importance in Western societies, as the culture of fear and the risk society make threats appear omnipresent. It portrays a context characterized by danger, uncertainty, insecurity, and fear, providing a dark, terrifying, and pessimistic view of the world that could benefit certain social actors. In response, the present work proposes a methodological approach based on the critical analysis of discourse and the activating aspects of fatalism to determine whether a discourse intends to create/reflect an atmosphere marked by fear and how the written/spoken component, as well as the audiovisual components, operate to construct such an atmosphere. The article presents an analysis sheet and explains its applicability to a case study on the discourse about immigration by the political party Vox on YouTube. Some of the conclusions include the resort to uncertainty and uncontrollability as axes of fatalism, as well as the Manichaean positioning that arises from using the savior strategy.